Dubai, the City as Corporation - Kanna, Ahmed (Book collections on Project MUSE., 2011)
Somewhere in the course of the late twentieth century, Dubai became more than itself. The city was, suddenly, a postmodern urban spectacle rising from the desert--precisely the glittering global consumer utopia imagined by Dubai's rulers and merchant elite. In "Dubai, the City as Corporation," Ahmed Kanna looks behind this seductive vision to reveal the role of cultural and political forces in shaping both the image and the reality of Dubai. Exposing local struggles over power and meaning in the making and representation of Dubai, Kanna examines the core questions of what gets built